Re-institute website - RE!NSTITUTE (2023)
We are a dynamic non-profit organization with a unique approach to man aging change and catalyzing innovation to support global systems trans formation. We know that to achieve equal, just, and safe communities, we must collectively challenge and change the systems that people rely on — especially those most vulnerable. Together, we must RE!BUILD a s ystem's resilience and capacity to take on our biggest generational ch allenges. Justice, housing, health, and other systems in every country are often struggling to come together, across institutions and organi zations, to unite under a common vision for change, and implement thos e changes in effective and innovative ways. Our work and methodology — the 100-Day Challenge — are designed to support these systems to achi eve extraordinary results. Our approach is rooted in the philosophy th at frontline staff, supported by leadership, can unleash innovation an d achieve incredible results by creating new relationships, experiment ing with fresh ideas from across their system, and building authentic engagement with those with lived experience.